Parasite immunity: Leishmania and Schistosoma - Gadelha, Catarina (Henry Stewart Talks, 2022)
Introduction to leishmaniasis, Life cycle of Leishmania, Mechanism of host-cell invasion by Leishmania- Transmission of Leishmania, The involvement of the immune system in leishmaniasis, Introduction to schistosomiasis (bilharzia), Life cycle and distribution of Schistosoma, Immune response and immune modulation during infection of Schistosoma, Chronic infection of Schistosoma